Multi-center and multi-vendor evaluation study across 1.5 T and 3 T scanners (part 1): apparent diffusion coefficient standardization in a diffusion MRI phantom - Pasini, Siria; Ringgaard, Steffen; Vendelboe, Tau; Garcia-Ruiz, Leyre; Strittmatter, Anika; Villa, Giulia; Raj, Anish; Echeverria-Chasco, Rebeca; Bozzetto, Michela; Brambilla, Paolo; Aastrup, Malene; Hansen, Esben S. S.; et al. (Magnetic resonance materials in physics, biology and medicine, 2025)
To validate multi-site and multi-vendor ADC measurements using the QIBA/NIST diffusion MRI phantom at room temperature.